Single high scrotal incision orchidopexy for unilateral palpable testis: A randomised controlled study - Almoutaz A. Eltayeb (Wolters Kluwer Medknow Publications, 2014)
Background: Bianchi and Squire introduced single high trans-scrotal incision for mobilisation of palpable undescended testes to decrease the potential morbidity of the traditional inguinal approach. This incision has not gained widespread acceptance and there is still a considerable debate about its efficacy. This study evaluated the outcome of high single scrotal incision in comparison to the classic inguinal exploration for unilateral palpable testes regardless to its pre-operative location to assure its validity and safety. Patients and Methods: This was a randomised controlled study conducted on seventy males with palpable unilateral undescended testicles from November 2009 to October 2013. They were divided into two equal groups; group I had high single scrotal incision and group II had the classic inguinal approach. The comparative parameters between both groups were the operative time, intra-and post-operative complications, post-operative pain and scar. Results: There was statistical significant difference between both groups regarding the operative time (P < 0.001). The high scrotal approach (Group I) was not completed in three cases and were converted to the classic inguinal approach. No statistical significant difference between both groups regarding the post-operative complications. Conclusions: Single high scrotal incision orchidopexy for palpable undescended testis is safe, has shorter operative time but may not be suitable for proximally lying testis.